Investigation on Physical and Mechanical Properties of Nanocomposites Made From Flour Of Pistachio Shell/ Corn Starch/ Nanoclay - ایمان کاریان (Regional Information Center for Science and Technology (RICeST), 2014)
In this study, effects of the flour of cellulosic shell of Pistachio and nanoclay loading on the physical and mechanical properties of wood plastic composite were investigated. Hence, flour of cellulosic shell of Pistachio, in levels of 30, 40 and 50 and Nano clay of cloisite 15A in three levels (0, 3 and 5%) was mixed with Corn starch polymer. Samples were made with a laboratory twin-screw extruder and then injection molding. The heating temperature proﬁle and rotational speed of the screws were set at 180–170–160–160 oC and 60 rpm, respectively. Mechanical properties including tensile and flexural properties as well as notched impact strength and physical properties including water absorption and thickness swelling were measured. The results showed that flexural and tensile strength, water absorption of the samples increased as the flour content increased from 30 to 50% (w/w), but tensile modulus, notched impact resistance and thickness swelling decreased. Furthermore, tensile modulus increased as the Nannoclay content increased from 0 to 5% (w/w). Besides, Flexural and tensile strength, Flexural modulus, notched impact resistance increased as Nannoclay content increased from 0 to 3% (w/w). beyond this limit (to 5% (w/w)), they decreased.Water absorption and thickness swelling of the samples decreased as the Nannoclay content increased from 0 to 5% (w/w).